UNMET ADL/IADL NEEDS AND SECONDARY CONSEQUENCES AMONG OLDER ADULTS IN RURAL AND NON-RURAL SETTINGS. (11th November 2018) - Steinman, B; McKibbin, C; Carrico, C; Barry, R; Cuadrado, B; Johnson, T; Longstreth, M; Slosser, A
Abstract: Marked disparities in key health-related outcomes are widely reported between rural and non-rural older adults. Many older individuals in rural regions experience greater incidence of chronic disease and functional impairment compared to non-rural counterparts. Compounding these disparities, access to services that address negative health outcomes is more likely to be limited in rural settings. The purpose of this study was to examine secondary consequences that result from unmet needs in activities of daily living (ADL) and instrumental activities of daily living (IADL). We compared the prevalence of ADL/IADL unmet needs in relation to rural/non-rural status of older adults. We looked at the association between unmet ADL/IADL needs and the following secondary consequences hypothesized to be associated with unmet ADL/IADL need: comorbidity, mortality, and relocation to a nursing home. Data came from two waves of the National Health and Aging Trends Survey (NHATS). Demographic covariates and independent variables related to ADL/IADL capacity and need came from the baseline (2011) wave; whereas dependent variables representing secondary consequences associated with unmet need came from the fifth wave (2015) of NHATS. Analyses included descriptive statistics of key independent and dependent variables, as well as logistic regression to estimate the association between ADL/IADL unmet need and each secondary consequence. We found that rural older adults not only experienced greater unmet ADL/IADL need compared to non-rural participants, but were also at greater risk for chronic disease, death, and nursing home placement associated with their unmet needs.